2017
DOI: 10.1007/s12072-017-9792-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of sorafenib therapy in hepatocellular carcinoma patients with failure of transarterial chemoembolization

Abstract: Sorafenib is a potential rescue therapy in patients with TACE failure. However, the clinical benefits need to be further evaluated for patients with main (or lobar) PVI or those treated with reduced doses of sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…The OS in our study was 4.1 to 6.4 months, whereas other practice-based studies have reported survival of 7.4 to 25.4 months in patients, given sorafenib as rescue therapy after TACE refractoriness. 7,16,17,26,27 Discrepancy may reflect differences in the distribution of patients between our study and the previous studies. In the present study, we included patients with CPC B (34.0%) and BCLC stage C (76.6%) HCC, whereas previous studies had excluded patients with CPC B of BCLC stage C HCC.…”
Section: Discussioncontrasting
confidence: 79%
“…The OS in our study was 4.1 to 6.4 months, whereas other practice-based studies have reported survival of 7.4 to 25.4 months in patients, given sorafenib as rescue therapy after TACE refractoriness. 7,16,17,26,27 Discrepancy may reflect differences in the distribution of patients between our study and the previous studies. In the present study, we included patients with CPC B (34.0%) and BCLC stage C (76.6%) HCC, whereas previous studies had excluded patients with CPC B of BCLC stage C HCC.…”
Section: Discussioncontrasting
confidence: 79%
“…Macroscopic vascular invasion: It is widely acknowledged that the presence of macroscopic vascular invasion leads to a poorer prognosis[ 26 , 30 ]. The meta-analysis by Peng et al[ 31 ] confirmed its prognostic value and the pooled analysis by Bruix et al[ 6 ] affirmed the importance of macroscopic vascular invasion as a predictor of survival but not of response to treatment.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…Our study demonstrated that the OS of the TACE-refractory group was shorter than that of the TACE-non-refractory group in both the study cohort (540 vs. 1,257 days, p 0.019) and validation cohort (568 vs. 1,324 days). These data indicated that TACE refractoriness, which was associated with the number of tumors and bilobular invasion, could contribute to poor prognosis and impair patients' OS (Johnson et al, 2016;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the JSH 2014 definition of TACE refractoriness was chosen because it has been widely accepted by radiologists for relatively easy application. As the earliest definition released, many researchers referred to this version for TACE refractoriness, and examples include Hiraoka A. et al (Hiraoka et al, 2015) and Lee S. et al (Lee et al, 2017 CT and serum AFP results after patients received two consecutive, adequate TACE procedures.…”
Section: Discussionmentioning
confidence: 99%